Speech without a Speaker: Constitutional Coverage for Generative AI Output? - Marco Bassini (European Constitutional Law Review)
Generative AI systems’ output as speech – Constitutional coverage for AI speech in the absence of a (human) speaker – Right of individuals to receive information as a perspective for framing constitutional coverage of generative AI output – Implications of constitutional coverage for content policing and content moderation by private platforms – Trends in the interpretation of existing content moderation regimes and their applicability to generative AI systems.